Models of and approaches to the station management of six African community radio broadcasters - Manyozo, Linje; Linda, Goretti Nassanga; Lopes, Claudia (MedieKultur: Journal of media and communication research, 2012)
This article is a political economy critique that contributes to current scholarship on community radio and development by examining the question of the management of six networks from Mali, Mozambique and Uganda. This discussion argues that understanding the models and functions of management committees will go a long way towards contributing to conversations on how community radios could achieve social, institutional, financial and ideological sustainability. The article also examines how management committees approach their work in the age of new Information Communication Technologies (especially mobile phones, computers and the Internet), and whether there is a gender digital divide within such committees. At the centre of the current discussion, therefore, is an attempt to understand the flow and contestation of power within community radio management committees.